Estudos de inclusões fluidas e de química mineral em depósitos de ferro e isotópicos U-Pb e Lu-Hf na Suíte Borrachudos na borda leste da Serra do Espinhaço meridional: implicações para a evolução metalogenética no fim do Precambriano - Sylvio Dutra Gomes (2018)
The Picarrao and Liberdade deposits contain high-grade iron orebodies (> 65% Fe) hosted in the Guanhaes Group itabirite, that are associated with emerald-bearing pegmatite veins and bodies related to the anatexis of the Borrachudos Granite. Fluid inclusion studies in quartz veins associated with the high-grade orebodies show that medium to high salinities (25-28 wt% NaCl eq.) and temperatures (275-375 °C) fluids are associated with the silica leaching that led to the iron enrichment. Mineral chemistry studies by LA-ICP-MS in the iron oxides demonstrate that metasomatic processes were responsible for the mineralogical transformations of magnetite to hematite and for subsequent hematite recrystallization. These processes are related to the iron upgrade in the itabirite and the formation of high-grade orebodies. The oxidation of the magnetite to martite is associated with an enrichment in P and As, and depletion in Mg, Ti and Co; as observed in martite crystals compared to their matching kenomagnetite rims. On the other hand Ti and Mo are enriched in hematite crystals that recrystallized from martite. In this case Ti behaved as an immobile element, and its enrichment is accompanied by the depletion of most of the trace elements. A second stage of magnetite formation precipitated with quartz in discordant veins and is oxidized to martite-II. These quartz-martite-II veins contain low salinity and temperature fluid inclusions that record an episode of meteoric fluid influx. The results of the LA-ICP-MS analyses on the fluid inclusions from pegmatite and quartz veins associated with the high-grade iron bodies indicate the contribution of anatectic fluids in the evolution of the metasomatic events. Isotopic Lu-Hf and geochronological studies on the zircon grains of the Borrachudos Suite provide constrains of the tectono-magmatic events that affected the southern border of the Sao Francisco Craton and leaded to the formation of the associated iron and emerald deposits. The granite records magmatic crystallization in the 1740-1688 Ma time range, and A2-type geochemical signature. Zircon grains present hydrothermal and anatectic areas with Cambrian age that are related to the gravitational collapse of the final stages Brasiliano orogen. During this event the granite was deformed and metamorphosed in the amphibolite grade, leading to anatexis and the formation of large amount of pegmatite bodies. The Hf isotope data on the hydrothermal/anatectic areas indicate that during the metamorphic peak of the orogen (ca. 610 Ma) small amounts of partial melting were accompanied by hydrothermal fluids enriched in radiogenic Hf. During the Cambrian these fluids contributed to the high degree of partial melting leading to the formation of large amounts of hydrous melts (pegmatite), the formation of the emerald deposits and the high-grade iron orebodies in the Picarrao-Liberdade deposit.